Elevating the peasants into high-rise apartments: The land bill system in Chongqing as a solution for land conflicts in China?. (October 2016) - Yep, Ray; Forrest, Ray
Abstract: In recent years, the Chinese central government has become increasingly concerned about the loss of agricultural land and future grain security and regulation over land utilization has been tightened. Amidst the official rhetoric of a "New Socialist Countryside", local administrations across China came up with a novel form of land utilization involving the transfer of peasants into high rise apartments. The beauty of the scheme is that the supply of new land in the rural area (released by the peasants who have abandoned their traditional village houses) enables the municipal administration to initiate development and construction in other locations within its jurisdiction where the land value is higher. Chongqing introduced a further innovation in the form of a "land bill system" that greatly facilitates and securitizes land transactions. The conversion of construction land rights into a marketable financial document enhances the transparency of the transactions and reduces the cost of land deals. The paper provides an account of the genesis, implementation and evaluation of this new scheme. This institutional innovation seems to provide a win–win situation for all stakeholders. Nevertheless, peasants may suffer in the long run and the impact on rural governance may also be damaging. Highlights: A nuanced account of local innovation in exploiting peasants' land use rights for developmental purposes. Analysis of the prospect of local experimentation and political entrepreneurship in China's policy process. An in-depth analysis of the genesis and mechanism of the innovative "land bill" system experimented in Chongqing. Original data on the impact of land bill system.